Scale up fractionation of components from novel glabrous brown and yellow canary seeds (Phalaris canariensis L.) and techno-functional properties of the resulting protein isolates. (November 2020) - Achouri, Allaoua; L'Hocine, Lamia; Martineau-Côté, Delphine; Sirois, Stéphane; Pitre, Mélanie; Mason, Emily; Abdel-Aal, Elsayed M.; Hucl, Pierre
Graphical abstract: Highlights: Novel glabrous brown and yellow canary seeds have similar composition. Main glabrous canary seed proteins are prolamins and glutelins. Protein isoelectric precipitation at pH 5 resulted in the highest protein yield and recovery. High purity canary seed protein isolates were obtained. Canary seed protein isolate had higher foaming and emulsifying capacities than soy protein isolate. Abstract: Glabrous canary seed ( Phalaris canariensis L . ) is a novel true cereal grain produced primarily in Western Canada which has been approved for human consumption by the U.S. Food and Drug Administration and Health Canada in 2016. Due to its high protein content (22%), this new edible grain is emerging as an alternative source of plant proteins. In the present work, protein extractability from four novel glabrous (2 yellow and 2 brown) canary seeds varieties was improved based on the selection of optimal pH of protein solubilisation and precipitation. Solubilisation at pH 12 followed by acid precipitation at pH 5 were retained as optimal conditions. Scale up of the protein optimized wet fractionation process resulted in highly purified canary seed protein isolates (purity of 91 to 93%) with protein recovery yield of 65 to 69%. In parallel, for the others canary seed components, a good recovery yields were obtained for the oil fraction (6.1–6.7 g/100 g flour), starch fraction (48.1–54 g/100 g flour), and crude fiber fraction (15.1–19.7 g/100 g flour). The study of the functional properties of the obtained canary protein isolates revealed, higher solubility at acidic than alkaline region; enhanced fat and water holding capacities and notably higher foaming and emulsifying capacities than control soy protein isolate. With growing global demand for protein, glabrous canary seed has high potential in the food industry, particularly as a good source of functional gluten free cereal proteins.